The Educator Resource Management In Improving Teacher Professionalism In MTS Muqaddimatul Akhlak Silo Jember - HASANAH, Nabila; TSAURI, Sofyan; USRIYAH, Lailatul (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:Educator Resource Management is a process of using competent human resources through the process of recruitment, selection, placement, training, and development to achieve the goals of educational institutions and professional teachers. The purpose of this research is to find out how the process of recruitment and selection of teaching resources. 2) To determine the placement of educational resources d. 3) To find out the training and development of educator resources.Methodology:This study uses a qualitative approach to the type of research Field research. Sources of data using primary data sources and secondary data sources. Data collection techniques using non-participatory observation, interviews, and documentation. Data analysis used descriptive qualitative with Miles and Huberman's interactive model. Data validity uses source triangulation and data triangulation.Findings:The recruitment process applies the principles of professionalism and transparency. b) The MTS Muqaddimatul Akhlak Silo Jember selection included administration selection, interviews, and teaching practice. 2) Placement of educators decided by the Head of the Madrasah is carried out by determining the background of the diploma, prioritizing work experience and abilities (skills), and paying attention to the attitude and appearance of prospective educators who will apply. 3). Training and development at Mts Muqaddimatul Akhlak Silo Jember.Implication:To improve and develop the potential of these teachers, the school organizes Training and workshops held by other agencies with the hope that the potential and knowledge of teachers will increase and develop so that they positively affect school progress.